DETERMINATION OF MASTICATORY EFFICIENCY IN PATIENTS WITH FIXED FULL IMPLANT-SUPPORTED PROSTHESES: DYNAMIC STUDY - Mostovei Mihail; Andrei Mostovei; Carmen Tiutiucă; Alina Ramona Dimofte; Arnaut Oleg; Solomon Oleg (Romanian Society of Oral Rehabilitation, 2022)
Introduction. There are multiple methods described in literature about chewing efficiency evaluation. The Gravimetric method was firstly introduced in 1901 and is still used nowadays for assessment of implant-prosthetic treatment. Aim. Dynamic evaluation of masticatory efficiency in full fixed implant supported restorations. Material and Methods. There were 63 patients included in this study from which 43 women and 20 men. Patients were divided in two groups: study group (33 edentulous patients) and control group with 30 (dentate patients). Patients from study group received 204 dental implants that were immediately loaded with provisional acrylic dentures. The evaluation of masticatory efficiency was performed using 5g of almonds that were chewed until swallowing reflex appears, counting the number of chewing cycles as well. The test was performed immediately after fixation of the prostheses and repeated after 6 months. Results. After statistical analysis, 3 out of 4 parameters had significant differences. These differences were found between the control and study groups both immediately after prosthesis fixation and 6 months after. However, there were no difference within the study group at different periods of time (initial and 6 months after). Conclusions. The use of implant-supported prostheses increase the quality of life, esthetics, confidence and masticatory efficiency of full edentulous patients. However, the last one still remains lower than in dentate patients.